Aborted myocardial infarction in ST-elevation myocardial infarction: insights from the STrategic Reperfusion Early After Myocardial infarction trial. Issue 19 (10th June 2014) - Maleki, Neda Dianati; Van de Werf, Frans; Goldstein, Patrick; Adgey, Jennifer A; Lambert, Yves; Sulimov, Vitaly; Rosell-Ortiz, Fernando; Gershlick, Anthony H; Zheng, Yinggan; Westerhout, Cynthia M; Armstrong, Paul W
Abstract : Background: We evaluated the prespecified endpoint, aborted myocardial infarction (AbMI), according to the use of a pharmacoinvasive (PI) strategy versus primary percutaneous coronary intervention (PCI) in 1754 patients randomised within 3 h of symptom onset in the STrategic Reperfusion Early After Myocardial infarction (STREAM) trial. Methods: Based on sequential ECG's and biomarkers, AbMI was defined as ST-elevation resolution ≥50% (90 min posttenecteplase (TNK) in the PI arm or 30 min postprimary PCI) with minimal biomarker rise. Results: In the PI arm 11.1% (n=99) had AbMI versus 6.9% (n=59) in primary PCI arm (p<0.01). In a multivariable model, AbMI patients overall had less baseline ΣST-deviation, fewer baseline Q-waves and shorter total ischaemic times. PI AbMI patients had faster time to TNK (90 vs 100 min, p=0.015): total ischaemic time was 100 min longer in primary PCI AbMI patients and no difference in ischaemic time existed between AbMI and non-AbMI patients within this group. Although no significant interaction between treatment and AbMI on the composite endpoint of death/shock/congestive heart failure/recurrent MI occurred (p=0.292), PI AbMI patients had a lower incidence in this endpoint than non-AbMI patients (5.1 vs 12%, p=0.038); this was not evident in primary PCI patients. Forty-five patients (ie, 2.5%) had masquerading MI with minimal biomarker elevation and no evolution in baseline ST-elevation. Conclusions: A PI strategy of early fibrinolysis more frequently aborts MI than primary PCI. Such PI patients had more favourable outcomes as compared with non-AbMIs. Diligent review of ECG evolution in STEMI distinguishes AbMI from infarct masquerade. Clinical Trials.gov ID: NCT00623623.